Sharing transboundary rivers - Moller, Lars Christian (2005)
This thesis is a collection of three essays on the economics of transboundary river management (contained in chapters 2-4) the contents of which is outlined below: Chapter 2 examines the equity-efficiency trade-off on a transboundary river where an upstream and a downstream riparian withdraw irrigation water. Equity is defined as ‘equal sharing of waters’ - a notion consistent with egalitarianism and equality of opportunity. Property rights are undefined, a priori, but riparians can enter an equal quota cooperative agreement (with side payments and restricted trade in water quotas). We find that the equity-efficiency trade-off is relatively insignificant, in prevalence as well as magnitude, and limited to special cases where the upstream riparian has a substantial relative cost advantage and/or water is very scarce. Chapter 3 examines a transboundary river conflict arising when upstream hydropower water releases do not coincide with the seasonal irrigation needs of a downstream riparian. We consider and rank the qualitative impact of a range of infrastructure investments, potentially initiated and co-financed by multilateral development banks (MDBs). Basinwide social efficiency and regional stability can, under certain conditions, be improved through Pareto-improving investments, including enhancement of upstream hydropower efficiency and expansion of downstream reservoir capacity. The findings are used to analyse proposed infrastructure projects in the Syr Darya Basin shared by Kyrgyzstan, Uzbekistan and Kazakhstan.